Identification of novel secreted fatty acids that regulate nitrogen catabolite repression in fission yeast - Sun, Xiaoying (Sci Rep, 2016)
Uptake of poor nitrogen sources such as branched-chain amino acids is repressed in the presence of high-quality nitrogen sources such as NH(4)(+) and glutamate (Glu), which is called nitrogen catabolite repression. Amino acid auxotrophic mutants of the fission yeast Schizosaccharomyces pombe were unable to grow on minimal medium containing NH(4)Cl or Glu even when adequate amounts of required amino acids were supplied. However, growth of these mutant cells was recovered in the vicinity of colonies of the prototrophic strain, suggesting that the prototrophic cells secrete some substances that can restore uptake of amino acids by an unknown mechanism. We identified the novel fatty acids, 10(R)-acetoxy-8(Z)-octadecenoic acid and 10(R)-hydroxy-8(Z)-octadecenoic acid, as secreted active substances, referred to as Nitrogen Signaling Factors (NSFs). Synthetic NSFs were also able to shift nitrogen source utilization from high-quality to poor nitrogen sources to allow adaptive growth of the fission yeast amino acid auxotrophic mutants in the presence of high-quality nitrogen sources. Finally, we demonstrated that the Agp3 amino acid transporter was involved in the adaptive growth. The data highlight a novel intra-species communication system for adaptation to environmental nutritional conditions in fission yeast.